Effects of local guidelines on prescribing practice and treatment outcomes in a long-stay psychiatric facility - Iličković Ivana M.; Tomčuk Aleksandar B.; Djedović Jovo M.; Bećir Kristina B.; Janković Slobodan M. (Srpsko lekarsko drustvo, 2019)
Introduction: a gap between evidence-based recommendations for prescribing antipsychotics and its implementation in practice could be overcome by local guidelines. Aim: the aim of our study was to locally adapt the national guideline for schizophrenia and evaluate its impact on prescribing practice as well as on clinical and humanistic outcomes in a long-stay psychiatric hospital Dobrota in Kotor, Montenegro. Subjects and Methods: This was academic, prospective, IV phase interventional study, which measured outcome before and after investigators intervention within healthcare system. The study was conducted in two six-months phases separated by implementation of the local guidelines. Prescribing practices and treatment outcomes were monitored in both phases of the study. Results: Study included 111 patients. Although the guidelines did not influence total volume of prescribed antipsychotics, social functioning and environmental aspects of quality of life were improved. Conclusions: Writing and adopting the guidelines for local use might be associated with some benefit in humanistic outcomes, but multi-faceted intervention should be considered in order to achieve more substantial impact on prescribing practices and clinical outcomes.